2010
DOI: 10.1016/j.ahj.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the amyloidogenic transthyretin Val 122 Ile allele in African Americans in the Arteriosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies

Abstract: Many African-Americans carry an amyloidogenic transthyretin mutation (TTR V122I), with a high risk for cardiac TTR amyloid deposition after age 65. We wished to determine the allele frequency and its clinical penetrance in community-dwelling African-Americans.Study subjects-5000 consenting African-Americans, ages 41 to 93, in two community studies of cardiovascular risk (CHS and ARIC).Methods-genotyping of banked DNA for TTR V122I allele status; review of cardiovascular and demographic parameters in CHS and AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 37 publications
(33 reference statements)
3
72
0
2
Order By: Relevance
“…1) (17,18). This allele occurs in 3% to 4% of African-American subjects (∼1.3 million people) and is hypothesized to contribute to the increased prevalence of heart failure among African Americans (14,15,17,19). WT-TTR aggregation underlies the development of senile systemic amyloidosis (SSA), a condition that affects as much as 10% to 20% of the population older than age 65 y and, in some patients, leads to progressive congestive heart failure (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) (17,18). This allele occurs in 3% to 4% of African-American subjects (∼1.3 million people) and is hypothesized to contribute to the increased prevalence of heart failure among African Americans (14,15,17,19). WT-TTR aggregation underlies the development of senile systemic amyloidosis (SSA), a condition that affects as much as 10% to 20% of the population older than age 65 y and, in some patients, leads to progressive congestive heart failure (20,21).…”
mentioning
confidence: 99%
“…S1) (11). These mutations lead to hereditary TTR amyloidoses such as familial amyloid polyneuropathy (FAP) (12,13) and familial amyloid cardiomyopathy (FAC) (14,15), which are autosomaldominant conditions with varying ages of onset and penetrance depending on the TTR mutation and ethnic background of the carriers (summarized in Fig. 1).…”
mentioning
confidence: 99%
“…5,6 Furthermore, the most common inherited mutation in TTR, a valine-to-isoleucine substitution at position 122 (V122I or Ile122), has an accepted prevalence of 3% to 4% among US blacks and seems to be associated with the development of heart failure in elderly black patients. 7 Thus, as the population ages and longevity increases, the incidence of TTR cardiac amyloidosis, both wild type and variant, will likely increase.…”
Section: Article See P 195mentioning
confidence: 99%
“…15 According to statistics from the U.S. Census, as many as 1.5 million African Americans carry the Val-122-Ile mutation. 16 Data from the Beta-Blocker Evaluation in Survival Trial revealed that around one-tenth of all African Americans aged > 60 years are carriers of Val-122-Ile mutation.…”
Section: -13mentioning
confidence: 99%